2012
DOI: 10.3390/toxins4080620
|View full text |Cite
|
Sign up to set email alerts
|

Animal Toxins Can Alter the Function of Nav1.8 and Nav1.9

Abstract: Human voltage-activated sodium (Nav) channels are adept at rapidly transmitting electrical signals across long distances in various excitable tissues. As such, they are amongst the most widely targeted ion channels by drugs and animal toxins. Of the nine isoforms, Nav1.8 and Nav1.9 are preferentially expressed in DRG neurons where they are thought to play an important role in pain signaling. Although the functional properties of Nav1.8 have been relatively well characterized, difficulties with expressing Nav1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…Our analysis indicates that the number of studies prioritising the identification of specific molecular targets using isolated and well-defined peptide fragments has steadily increased overtime. The development of recent techniques such as site-directed mutagenesis, production of recombinant toxin variants and chimeric ion channel constructs, together with use of improved 3D modelling, has allowed greater understanding of toxin-channel interactions and the underlying mechanisms determining the SCTX selectivity and affinity (Gilchrist and Bosmans, 2012;Zhang et al, 2011Zhang et al, , 2012Gur et al, 2011;Gurevitz, 2012;Ma et al, 2013). Use of cloned ion channels within expression systems has been central to study of SCTX peptide action.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis indicates that the number of studies prioritising the identification of specific molecular targets using isolated and well-defined peptide fragments has steadily increased overtime. The development of recent techniques such as site-directed mutagenesis, production of recombinant toxin variants and chimeric ion channel constructs, together with use of improved 3D modelling, has allowed greater understanding of toxin-channel interactions and the underlying mechanisms determining the SCTX selectivity and affinity (Gilchrist and Bosmans, 2012;Zhang et al, 2011Zhang et al, , 2012Gur et al, 2011;Gurevitz, 2012;Ma et al, 2013). Use of cloned ion channels within expression systems has been central to study of SCTX peptide action.…”
Section: Discussionmentioning
confidence: 99%
“…AmmVIII and AaH1 were found not to alter the Nav1.9 current in DRG neurons (Abbas et al, 2013). Recent publications have suggested that Tityus bahiensis scorpion venom (TbScV) (Moraes et al, 2011) and TsVII (Tityus serrulatus) (Gilchrist and Bosmans, 2012) have potential action on Nav1.8 and Nav1.9 channels, although this requires further assessment and characterization.…”
Section: Scorpion Venom Peptide Actions On Voltage-gated Sodium Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxins isolated from the venom of Thrixopelma pruriens, Ceratogyrus cornuatus and Phrixotrichus auratus constitute very promising molecules since they are reported to inhibit the different subtypes of voltage gated sodium channels (Nav): Nav1.7 and Nav1.8 [16,17]. These subtypes of channels are related to pain signaling, since they are selectively expressed in peripheral sensory neurons and contribute for the transmission of the pain signal [18]. In addition, toxins which block voltage gated calcium channels may induce anti-nociception and are found in the venom of Selenocosmia huwena, Grammostola rosea, Agelenopsis aperta and Phoneutria nigriventer [5,13,14,19,20].…”
Section: Appro Poult Dairy and Vet Scimentioning
confidence: 99%
“…8 Na V 1.9 is also a desirable drug target (as shown using mouse models) and is also expressed in DRG neurons but has proved difficult to functionally express in heterologous systems and is therefore challenging to study. 9 TRPV1 (a member of the TRP superfamily of excitatory ion channels that bind vanilloids) is predominantly expressed by nociceptors and is therefore also a popular pain relief target, 10 but in clinical trials, drugs inhibiting the TRPV1 channel cause hyperthermia and decreased sensitivity to painful levels of heat. To overcome these life-threatening side effects, Fischer et al, 11 developed tools to block phosphorylation of TRPV1 instead of blocking the channel: this is effective through the disruption of TRPV1 interaction with A-kinase anchoring protein 79 (AKAP79).…”
Section: Pain Target Classesmentioning
confidence: 99%